A possible relation between new neuronal recruitment and migratory behavior in Acrocephalus warblers. Issue 12 (17th June 2014) - Barkan, Shay; Yom‐Tov, Yoram; Barnea, Anat
ABSTRACT Evidence suggests a possible correlation between learning abilities of adults and new neuronal recruitment into their brains. The hypothesis is that this brain plasticity enables animals to adapt to environmental changes. We examined whether there are differences in neuronal recruitment between resident and migrant birds. We predicted that migrants, which are more exposed to spatial changes than residents, will recruit more new neurons. To test this, we compared neuronal recruitment in two closely related bird species ‐ the migrant reed warbler (Acrocephalus scirpaceus), and the resident Clamorous warbler (A. Stentoreus) ‐ during spring, summer, and autumn. Wild birds were caught, treated with BrdU and sacrificed five weeks later. New neurons were recorded in the Hippocampus and Nidopallium caudolateral. The results support our hypothesis, as more new neurons were found in the migrant species, in both brain regions and all seasons. We suggest that this phenomenon enables enhanced navigational abilities, which are required for the migratory lifestyle. However, in contrast to our hypothesis, in spring we found less new neurons in adults of both species, as compared to other seasons. We suggest that in spring, when birds settle in breeding territories, they require less spatial skills, and this might enable to reduce the cost of neuronal recruitment, as reflected by less new neurons in their brains. We also found age differences, with overall higher neuronal recruitment in juveniles. Finally, we advocate the importance of studying wild populations, for a better understanding of the adaptive significance of neuronal replacement in the vertebrate brain. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 74: 1194–1209, 2014